Basis trends in North Carolina and their effect on corn prices - Marshall, Dana (Kansas State University, 2017)
Livestock production is a crucial industry in North Carolina. Broilers, turkeys, and hogs all have tremendous amounts of production numbers that are steadily growing particularly on the broiler side. This thesis seeks to explore the trends in three basis indicators and explore their effects on corn prices in North Carolina. Given the significant role corn plays in livestock production in the state and the deficit situation it finds itself in with respect to corn, these analyses may illuminate some challenges that may adversely affect the long term competitiveness of the poultry industry in the state. Already, hog and turkey production seems to be migrating out of the state possibly due to feed costs. The importance of this study is to help identify innovative solutions to arrest the increasing adverse effects of feed costs on North Carolina’s livestock industry. Using statistical analyses and data on corn prices and three basis indicators, CSX-90, Norfolk-Southern 75, and Truck Only, we show that while corn prices, on average, have declined slightly over the past several years, the transportation costs associated with moving corn into North Carolina have increased for all three options evaluated. The average growth rate in CSX 90 was approximately 7.4% per annum compared to 7.7% for NS-75 and 12.4% for truck only. Thus, while average annual trucking costs were lower than the rail transportation by between 82% and 92%, it was growing at more than 50% the growth rate in rail prices. Interestingly, we observe that the difference between the paired basis were all statistically significant at the 1% level. For this example the difference between the monthly average CSX 90 and trucking only was about $0.29, with a t-statistic of 17.34 and a p-value of 0.00. Similarly, the difference between the monthly average CSX-90 and NS-75 was $-.04, with a t-statistic of 3.35 and a p-value of 0.00. The foregoing reveal the advantage of sourcing corn via trucking given its lower basis. However, the higher variability in trucking compared to rail and the rapid growth rate in trucking suggests that an innovative strategic approach be adopted to overcome its potential long-term effect on corn prices. We show that a careful assessment of what the livestock industry in North Carolina is currently doing and what it needs to do could shed light on how to deal with this situation. Fixed assets like feed mills, production facilities, and slaughter facilities determine the type of access to outside rail or access to local markets. These assets are unlikely to change and therefore it is important to build an efficient supply chain to decrease marginal costs.
Keywords: Basis; Rail; Corn